Prolonged hippocampal cell death following closed-head traumatic brain injury in rats. Issue 10 (6th July 2016) - Tsuda, Shigeharu; Hou, Jiamei; Nelson, Rachel L.; Wilkie, Zachary J.; Mustafa, Golam; Sinharoy, Ankita; Watts, Joseph V.; Thompson, Floyd J.; Bose, Prodip K.
Abstract : Traumatic brain injury (TBI) leads to enduring cognitive disorders. Although recent evidence has shown that controlled cortical impact in a rodent may induce memory deficits with prolonged cell death in the dentate gyrus (DG) of the hippocampus, few studies have reported long-term chronic hippocampal cell death following 'closed-head' TBI (cTBI), the predominant form of human TBI. Therefore, the aim of this study was to quantify terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)(+) apoptotic hippocampal cells as well as hippocampal cells with hallmark morphological features of degenerating cells in a chronic setting of cTBI in rats. TUNEL assays and Cresyl violet staining were performed using 6-month post-TBI fixed hippocampal sections. Evidence of prolonged hippocampal cell death was shown by the presence of a significantly increased number of TUNEL(+) cells in the cornu ammonis 1–3 (CA1–CA3) and DG of the hippocampus compared with intact controls. In addition, Cresyl violet staining indicated a significantly elevated number of cells with the degenerative morphological features in all hippocampal subregions (CA1–CA3, hilus, and DG). These results suggest that prolonged cell death may occur in multiple regions of the hippocampus following cTBI.